Understanding Lithic Recycling at the Late Lower Palaeolithic Qesem Cave, Israel : a Functional and Chemical Investigation of Small Flakes. - Venditti, Flavia (Archaeopress archaeology., 2019)
Qesem Cave (Israel) acts here as a case study to explore two important topics from the Middle Pleistocene: the practice of recycling old discarded flakes for the production of new objects by means of recycling, and the production of flakes and tools of small dimensions--topics that have not gained sufficient attention from the scientific community.